The professional literature used by American and French agronomists and the implications for agronomic education - Lawani, S.M. (1977)
A sample containing 1,373 citations were taken from three American and three French agronomic journals and analyzed to provide information on the age, languages, origins, and types of literature used by American and French agronomists. Of the American citations, 97.7% were in English and 77.5% were of North American origin. French agronomists used a significantly higher proportion of literature from other countries and in languages foreign to them than American agronomists. American agronomists overlook relevant and potentially valuable literature published in other parts of the world, and language is the responsible factor. French agronomists use unpublished literature more than did American agronomists. The results suggest that graduate programs in agronomy should review the policy of reduced requirements of foreign languages. The study of subject literatures, indexing and abstracting services, other bibliographical data bases, as well as translation services, should be formalized in graduate schools. Some of the most cited journals and all the journals cited by both American and French agronomists are listed.